Relação entre fatores de risco e desenvolvimento psicomotor, de linguagem e de cognição nos dois primeiros anos de vida - Nunes, Sabrina Felin (2019)
This thesis aimed to analyze the possible effects of psychic risk and clinical variables such as Apgar 1 and 5 minutes, mechanical ventilation, intercurrence during gestation, smoking during pregnancy, having toys at home and type of breastfeeding, psychomotor development, cognitive and language, in infants of 18 and 24 months of age. To do this, we performed correlation and association analyzes between the results of Bayley Scales of Infant and Toodler Development®, Third Edition (Bayley III) at 18 and 24 months and the results of the psychic tests, Program of Studies and Research in Autism (PREAUT) at 9 months, Child Development Risk Indicators (IRDI) (total score), Modified Checklist for Autism in Toodlers (M-CHAT) at 18 and 24 months, and clinical variables. The association between the Prechtl General Movements Method (PGM) and Bayley III was also performed with the psychic and study variables already mentioned. Statistical analysis with the Bayley III Scale was composed of 47 infants, and this number varied according to participation in all stages of the study. For the analysis with the PGM Method, the total number of participating infants was 42. As a result of this research, 55.3% of the infants were male and 44.7% female, the mean gestational age at birth was of 37 weeks and 1 day, of which 59.6% were born full term, 27.7% were premature, 8.5% were preterm and 4.2% were preterm infants. Regarding the variables of the study, only breastfeeding presented a statistically significant result with the Bayley III cognitive test at 18 months (p = 0.048), with the mean being better in exclusive breastfeeding (113.8), followed by the mixed (95.6) and artificial (86.2). Bayley III presented association and correlation with the M-CHAT protocol, especially at 18 months, showing that the better the results in Bayley III the lower the risks for M-CHAT, since it addresses issues to parents regarding the presence / absence of children's skills. No statistically significant differences were found between the results of the PGM method at three months and the outcome with Bayley III at 18 and 24 months, since PGM is more effective with very premature infants and who presented with important neonatal complications. The results of this thesis allow us to conclude that it is important to carry out joint evaluations of child development, because it is known that the sooner the detection of some developmental risk / delay occurs, greater the success of the intervention.